Formation of (2R)- and (2S)-8-Prenylnaringenin Glucuronides by Human UDP-Glucuronosyltransferases - Fang, Jin-Bo (J Agric Food Chem, 2019)
Occurring in hops (Humulus lupulus) and beer as a racemic mixture, (2R,2S)-8-prenylnaringenin (8-PN) is a potent phytoestrogen in hop dietary supplements used by women as alternatives to conventional hormone therapy. With a half-life exceeding 20 h, 8-PN is excreted primarily as 8-PN-7-O-glucuronide or 8-PN-4’-O-glucuronide. Human liver microsomes and 11 recombinant human UDP-glucuronosyltransferases (UGTs) were used to catalyze formation of the two oxygen-linked glucuronides of purified (2R)-8-PN and (2S)-8-PN, which were subsequently identified using mass spectrometry and NMR spectroscopy. Formation of (2R)- and (2S)-8-PN-7-O-glucuronides predominated over the 8-PN-4’-O-glucuronides except for intestinal UGT1A10, which formed more (2S)-8-PN-4’-O-glucuronide. (2R)-8-PN was a better substrate for all 11 UGTs except for UGT1A1, which formed more of both (2S)-8-PN glucuronides than (2R)-8-PN glucuronides. Although several UGTs conjugated both enantiomers of 8-PN, some conjugated just one enantiomer, suggesting that human phenotypic variation might affect the routes of metabolism of this chiral estrogenic constituent of hops.